IMPLEMENTASI MANAJEMEN PERUBAHAN DALAM MENGEMBANGKAN SISTEM MENGHAFAL AL-QUR’AN DI MTS HIFZIL QUR’AN YAYASAN ISLAMIC CENTRE - Kurniawan, Rahmat; Damanik, M. Adlin; Amiruddin, Amiruddin (Hijri, 2021)
In general, this study aims to explain the leadership behavior of school principals in increasing teacher participation in performance at the Annur Prima Medan Islamic Private Junior High School. This research method uses qualitative research methods. Data collection techniques used in this study were observation, interviews and document studies. The data analysis techniques used in this research are data reduction, data presentation, and drawing conclusions.The results of the research that have been carried out by researchers show that the leadership behavior of the principal in increasing teacher participation in the performance of teachers at the Annur Prima Medan Islamic private junior high school has been carried out well. This is the science of determining morals and character so that with the amount of knowledge that already exists in accordance with what has been studied will greatly affect one's personality, especially being a school principal must be in accordance with what the world of education demands, which is to have an energetic personality so that it will be able to bring changes to the world of education, knowledge without morals is of no value, while morality without knowledge is unable to direct oneself, let alone others.Increasing the potential for quality performance, good communication will be carried out through gathering all subordinates so that the agenda for the joint meeting will be carried out properly then the principal will provide direction and guidance, with this it will be easy to evaluate all work programs that have been carried out together. Teacher motivation in improving its performance must start with sincerity, namely always providing knowledge to students without expecting anything in return. The next motivation is patience, namely teaching students like teaching their own children. Then, the motivation in improving teacher performance is in educating students with full responsibility and paying attention to students.Change Management Developing q System of Memory of The Qur'an